Origins of Sustainable Economic Growth (Nobel Prize in Economics, 2025) - Shymanska, Oksana (Herald of Economics, 2026)
The research of Joel Mokyr, Philippe Aghion, and Peter Howitt – laureates of the 2025 Nobel Prize in Economics – is pivotal for understanding the mechanisms of long-term sustainable economic growth. The scholars examined how integrating scientific knowledge and technology, adopting creative approaches to product development, and the process of creative destruction stimulate production renewal and enhance productivity. Their models demonstrate that sustainable growth emerges from the interaction of innovation, competition, and effective institutions that protect innovation and foster entrepreneurship. Research purpose. To substantiate the contribution of J. Mokyr, P. Aghion, and P. Howitt to the construction of sustainable economic growth models that explain the role of technological change, the process of creative destruction, and the interaction between scientific knowledge and technology. Research methods: systemic approach, methods of induction and deduction, analysis and synthesis, mathematical methods, and conceptual generalization. Results. A systematic analysis of the models of J. Mokyr, P. Aghion, and P. Howitt has been carried out, explaining the mechanisms of innovative renewal and creative destruction in achieving sustainable growth. The key factors of long-term productivity have been substantiated: knowledge and technology integration, the impact of technological shocks, and competition. The significance of creative approaches to product and technology development is emphasized, as they ensure continuous product renewal and lay the foundation for sustainable economic growth. Attention is given to institutional conditions that stimulate entrepreneurship, protect innovation, and strengthen competition, thereby ensuring long-term sustainable growth. Prospects. Further research should empirically test the models of Mokyr, Aghion, and Howitt at the level of individual industries and national economies, while accounting for the specifics of the competitive environment and institutions. Important areas include the analysis of the impact of emerging technologies, particularly artificial intelligence; financial constraints; firm heterogeneity; and patent protection, which will allow for the evaluation of the effectiveness of state innovation policy and the provision of long-term sustainable growth.